Ingestion of Carbohydrate-Rich Supplements during Gestation Programs Insulin and Leptin Resistance but not Body Weight Gain in Adult Rat Offspring - Beck, Bernard; Richy, Sébastien; Archer, Zoe A.; Mercer, Julian G. (Frontiers in Physiology, 2012)
Prenatal nutritional conditions can predispose to development of obesity and metabolic syndrome in adulthood. Gestation with its important hormonal status modification is a period of changes in usual feeding habits with pulses or avoidance for certain categories of food. We tried to mimic in an animal model some changes in food consumption patterns observed in pregnant women. For this purpose, Long-Evans female rats were fed during the dark period, their usual pre-gestational food quantity, and were allowed to complete their intake with either a control (Cr), high-fat (HF), or high-carbohydrate (HC) diet available ad libitum during the light period. Dams fed a control diet ad libitum (Ca) served as controls. Body weight and composition, food intake, and metabolic hormones (insulin, leptin) were recorded in male offspring until 20 weeks after birth. Cr and HC females ate less than Ca females ( -16%; p<0.001) and their offspring presented a weight deficit from birth until 6 (HC group) and 10 (Cr group) weeks of age (p<0.05 or less). Plasma leptin corresponded to low body weight in Cr offspring, but was increased in HC offspring that in addition, had increased plasma insulin, blood glucose and subcutaneous adipose tissue mass. HF dams ate more than Ca dams (+13%;p<0.001), but plasma leptin and insulin were similar in their offspring. Hypothalamic Ob-Rb expression was increased in Cr, HC and HF offspring (+33-100% vs. Ca; p<0.05 or less). HC supplement ingestion during gestation leads therefore to insulin and leptin resistance in adult offspring independently of lower birth weight. These hormonal changes characterize obesity-prone animals. We therefore suggest to be heedful of the carbohydrate content in the diet during the last weeks (or months) preceding delivery to limit development of later metabolic disorders in offspring.